Geographic, Economic, and Political Determinants of Military Emergency Rule in Aceh, 1998–2005 - Murliana, Murliana; Saputra, Dian; Jumi Adela Wardiansyah; Istantiani, Meinita; Syukri, Syukri (Unisia, 2025)
This study examines the factors behind the imposition of Military Emergency Status in Aceh between 1998 and 2005, a period marked by prolonged armed conflict between the Government of Indonesia and the Free Aceh Movement. The article aims to explain why the state ultimately resorted to military emergency rule by analyzing the interaction of geographic, economic, and political conditions that shaped the conflict. Using a qualitative library-based research design, the study relies on historical analysis of books, academic articles, official regulations, and credible reports related to the Aceh conflict. The collected materials are critically reviewed, categorized, and interpreted to reconstruct the policy context and conflict dynamics leading to the declaration of military emergency. The findings show that Aceh’s strategic geography, particularly in Aceh Timur and surrounding areas, facilitated mobility, logistical access, and cross-regional connections that strengthened armed resistance. Economically, despite abundant natural resources, local communities experienced marginalization, limited participation in resource management, and persistent inequality, which intensified social grievances. Politically, unresolved human rights violations during the previous Military Operations Area period, weak law enforcement, and declining public trust in civilian governance contributed to growing support for the Free Aceh Movement. The failure of peace negotiations and the escalation of violence further reinforced the state’s preference for a security-based approach. In conclusion, the study argues that the Military Emergency Status in Aceh was not a sudden policy choice but the result of accumulated geographic vulnerabilities, economic injustice, and political dissatisfaction. These findings highlight the importance of addressing structural inequalities and political accountability as essential lessons for conflict resolution and sustainable peacebuilding in post-conflict regions.